2017
DOI: 10.1007/s00125-017-4322-3
|View full text |Cite
|
Sign up to set email alerts
|

The VEGF-A inhibitor sFLT-1 improves renal function by reducing endothelial activation and inflammation in a mouse model of type 1 diabetes

Abstract: Aims/hypothesisAnimal models of diabetic nephropathy show increased levels of glomerular vascular endothelial growth factor (VEGF)-A, and several studies have shown that inhibiting VEGF-A in animal models of diabetes can prevent albuminuria and glomerular hypertrophy. However, in those studies, treatment was initiated before the onset of kidney damage. Therefore, the aim of this study was to investigate whether transfecting mice with the VEGF-A inhibitor sFlt-1 (encoding soluble fms-related tyrosine kinase 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 50 publications
5
43
0
2
Order By: Relevance
“…31 HG was showed to induce renal glomerular endothelial hyperpermeability by damaging the tight junction between cells. Growing evidence indicates that dysfunction of GEnCs could aggravate renal injury in DN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 HG was showed to induce renal glomerular endothelial hyperpermeability by damaging the tight junction between cells. Growing evidence indicates that dysfunction of GEnCs could aggravate renal injury in DN.…”
Section: Discussionmentioning
confidence: 99%
“…In the DN mice model, inhibiting VEGF-A could reduce endothelial activation and glomerular inflammation, therefore ultimately reversing kidney damage. 31 HG was showed to induce renal glomerular endothelial hyperpermeability by damaging the tight junction between cells. 32 In our study, we cultured GEnCs and then stimulated them with HG or chemerin.…”
Section: Serum Chemerin Level Was Closely Related With Renal Functionmentioning
confidence: 99%
“…VEGF-A inhibitor sFlt-1 (soluble fms-related tyrosine kinase 1) is observed to reverse renal impairment by decreasing albuminuria, glomerular hypertrophy, and mesangial matrix expansion in mice diabetic mice. In addition, as reflected by decreased levels of vascular cell adhesion molecule 1 (VCAM-1), it also reduced VEGF-A-induced endothelial activation ( Bus et al, 2017 ).…”
Section: The Role Of Vegf-a In Abnormal Angiogenesis Of Dnmentioning
confidence: 99%
“…It has been demonstrated that high glucose levels can increase proinflammatory molecules such as intercellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM)-1 in endothelial cells [ 14 ]. Recently, vascular endothelial growth factor-A inhibitor ameliorated renal inflammation in a mouse model of type 1 diabetes [ 15 ]. Thus, down-regulation of renal endothelial activation, especially in the early stage, may have a protective role against diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%